2002
DOI: 10.1289/ehp.021101105
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of pulmonary immunity to Listeria monocytogenes by diesel exhaust particles (DEPs). I. Effects of DEPs on early pulmonary responses.

Abstract: Diesel exhaust particles (DEPs), generated by heavy-duty diesel engines in various industries, can adsorb over 450 different organic compounds, including mutagenic and carcinogenic polycyclic aromatic hydrocarbons (1). With diameters < 2 µm, these fine respirable particles can remain airborne for long periods of time and deposit in great numbers deeply in the lungs. For these reasons, exposure of truckers, railroad and construction workers, and engine mechanics to DEPs is an occupational health concern. A repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 43 publications
(45 reference statements)
4
53
3
Order By: Relevance
“…This is different from that of the results in temperate regions where ILI (%) is positively correlated to the PM 10 concentration [19,20], the underlying mechanism is such that the increases in PM 10 reduce ultraviolet radiation reaching the ground which helps to the development of flu virus, therefore, more PM 10 leads to the acceleration of development and transmission of influenza virus. However, our knowledge of how ultraviolet radiation influences human's immunity system is less certain.…”
Section: The Correlation Between the Ili (%) And Ambient Conditionscontrasting
confidence: 82%
“…This is different from that of the results in temperate regions where ILI (%) is positively correlated to the PM 10 concentration [19,20], the underlying mechanism is such that the increases in PM 10 reduce ultraviolet radiation reaching the ground which helps to the development of flu virus, therefore, more PM 10 leads to the acceleration of development and transmission of influenza virus. However, our knowledge of how ultraviolet radiation influences human's immunity system is less certain.…”
Section: The Correlation Between the Ili (%) And Ambient Conditionscontrasting
confidence: 82%
“…Using larger doses of LM in a rat model, Yin and colleagues attributed the immunosuppressive effects of acute exposure to diesel exhaust particles to attenuation of early macrophage activation and cytokine release (43). The cytokine profiles obtained in our study 3 days after infection (Experimental Day 6) appeared to be very similar between uninfected animals pre-treated with PBS or both doses of SWCNT.…”
Section: Discussionsupporting
confidence: 55%
“…DEP suppress alveolar macrophage function, as demonstrated by reduced production of the cytokines IL-1β and TNF-α, and this suppression could impair normal host defenses [32][33][34][35] with these reports: level of IL-1β and TNF-α in BAL fluid were significantly decreased in both the C57BL/6 and BALB/c strains, but C57BL/6 mice showed a more marked decreased than BALB/c mice. This difference in reduction in macrophage function was also a mechanism of defense against DEPs that differed between hosts.…”
Section: Exp Lung Res Downloaded From Informahealthcarecom By Univermentioning
confidence: 67%
“…In contrast, our present results showed that after prolonged low-dose DEP exposure, the expression of GST in lung tissues decreased and the expression of HO-1 was unchanged. On the one hand, DEP exposure induces the expression of antioxidative stress enzymes via the antioxidant-responsive element in macrophages [11][12][13]; on the other, DEP exposure impairs macrophage function [32][33][34][35]. Therefore, we think that the decrease in GST expression in C57BL/6 mice may be involved in the impairment of macrophage function after prolonged DEP exposure, and that HO-1 expression contributed only in the early stages of DEP exposure.…”
Section: Exp Lung Res Downloaded From Informahealthcarecom By Univermentioning
confidence: 96%